THE KYIV PERIOD OF LIFE OF O.EIHELMANN: THE FORMATION AND DEVELOPMENT OF SOCIAL AND POLITICAL POSITIONS - Турчин, Я.Б. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The process of formation of social and political views of O.Eihelmann, namely the period before emigration is analyzed in the article. Different activities of the scientist: the scientific, educational and social and political are considered here. The combination of theoretical ideas of O.Eihelmann with state-forming practice is traced. It is proved that it was the Kyiv period of life of the scientist that became a turning point in asserting his social position which was completely ended in the emigration.